2013
DOI: 10.1093/rpd/nct049
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of absorbed and effective doses to patients from radiopharmaceuticals using the ICRP 110 reference computational phantoms and ICRP 103 formulation

Abstract: In diagnostic nuclear medicine, mean absorbed doses to patients' organs and effective doses are published for standard stylised anatomic models. To provide more realistic and detailed geometries of the human morphology, the International Commission on Radiological Protection (ICRP) has recently adopted male and female voxel phantoms to represent the reference adult. This work investigates the impact of the use of these new computational phantoms. The absorbed doses were calculated for 11 different radiopharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
14

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 17 publications
2
15
0
14
Order By: Relevance
“…The absorbed doses for 123 I (25% thyroid uptake) and 131 I (55% thyroid uptake) are compared in Tables 1 and 2, respectively. The organ doses calculated in this study were in good agreement with the values reported by Smith et al (2000), Zankl et al (2010Zankl et al ( , 2011, and Hadid et al (2013) within 7% on average. Some values for wall organs, however, showed larger differences; for example, the urinary bladder wall doses for 25% uptake of 123 I were 7.06 × 10 −2 (obtained from Zankl et al, 2011) and 3.69 × 10 −2 (calculated in this study) mGy (MBq)…”
Section: Resultssupporting
confidence: 89%
“…The absorbed doses for 123 I (25% thyroid uptake) and 131 I (55% thyroid uptake) are compared in Tables 1 and 2, respectively. The organ doses calculated in this study were in good agreement with the values reported by Smith et al (2000), Zankl et al (2010Zankl et al ( , 2011, and Hadid et al (2013) within 7% on average. Some values for wall organs, however, showed larger differences; for example, the urinary bladder wall doses for 25% uptake of 123 I were 7.06 × 10 −2 (obtained from Zankl et al, 2011) and 3.69 × 10 −2 (calculated in this study) mGy (MBq)…”
Section: Resultssupporting
confidence: 89%
“…The previously used mathematically describable MIRD-phantoms were developed using highly simplified organ shapes, which sometimes resulted in less realistic distances within and between organs. For a limited number of radiopharmaceuticals, and for adults, it has been shown that there is a difference between earlier estimations of the effective dose and the results of the calculations using the new ICRP/ICRU reference phantoms and the new ICRP tissue weighting factors [ 10 12 ]. The aim of this work was to use published biokinetic data [ 13 – 15 ] as a base for a complete recalculation of the effective dose for all radiopharmaceuticals hitherto published by the ICRP, using the new adult reference phantoms [ 6 ] and the ICRP publication 103 tissue weighting factors [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zankl et al 13 report that, when comparing calculations using voxel phantoms with calculations using stylized ("MIRD-type") phantoms, deviations between 50% and 100% can be obtained. And finally, Hadid et al 14,15 and Parach et al 16 reach similar conclusions, showing that when calculating dose coefficients with voxel phantoms and comparing them with a MIRD phantom, significant variations (up to few hundred percent) were obtained.…”
mentioning
confidence: 65%